2017
DOI: 10.1002/asjc.1486
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐Time Consensus Problem for Second‐Order Multi‐Agent Systems Under Switching Topologies

Abstract: This paper investigates the finite‐time consensus problem for multi‐agent systems with second‐order individual dynamics under switching topologies. A distributed continuous‐time protocol is designed to guarantee finite‐time consensus for homogeneous agents without predetermined leaders, i.e., it ensures agents asymptotically converge to an average consensus within finite time, even if the interaction topology among them is time‐varying but stepwise jointly‐connected. In particular, it introduces a distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Compared to some finite‐time controllers , the fixed‐time controller in this paper has an additional fractional power term with an index larger than 1, i.e. , 1+ab in and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to some finite‐time controllers , the fixed‐time controller in this paper has an additional fractional power term with an index larger than 1, i.e. , 1+ab in and .…”
Section: Resultsmentioning
confidence: 99%
“…Remark 3. Compared to some finite-time controllers [39][40][41][42][43], the fixed-time controller in this paper has an additional fractional power term with an index larger than 1, i.e., 1 + a b in (9) and (21). This power term ensures the containment control is achieved in a fixed time.…”
Section: Remarkmentioning
confidence: 99%
“…The results have shown that the effectiveness and validity are not only for the chained system, but also for traditional mobile vehicles. Based on the same switching topologies, a multiagent system with second-order separated dynamics addressed the finite-time consensus problem [7]. A distributed protocol was designed to guarantee a finite-time solution for homogeneous agents without predetermined leaders in continuous time domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, the consensus problems, such as the firstorder multiagent systems [9,10], the second-order multiagent systems [6,7,[11][12][13][14][15], the high-order multiagent systems [16,17], and the fractional-order systems [18,19], have been extensively considered. Compared with other multiagent systems, the second-order multiagent systems is more popular for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], the consensus tracking problem with disturbances and unmodeled dynamics was studied, and the consensus problem with communication delay was developed in [12]. Moreover, the formation control problem with time-varying delays and the finite-time consensus problem with switching topology were discussed as well [13][14][15].…”
Section: Introductionmentioning
confidence: 99%